2016
DOI: 10.1111/tid.12579
|View full text |Cite
|
Sign up to set email alerts
|

Viral load and ganciclovir (GCV) concentration in cerebrospinal fluid of patients successfully treated with GCV or valGCV for human herpesvirus 6 encephalitis/myelitis following umbilical cord blood transplantation

Abstract: We describe successful treatment of 3 cases of human herpesvirus 6 (HHV-6) encephalitis/myelitis following cord blood transplantation (CBT). Ganciclovir (GCV) (10 mg/kg/day) reduced HHV-6 load to undetectable levels in cerebrospinal fluid (CSF). Early dose reduction in the presence of HHV-6 detectable in CSF resulted in an increased HHV-6 load. GCV was capably shifted to valganciclovir (VGCV) with an almost equivalent concentration. GCV/VGCV may be effective for HHV-6 encephalitis/myelitis after CBT, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…As described above, various background factors are different between pediatric and adult HSCT recipients, but present study and together with the previous studies mainly analyzed adult patients suggest that there are any differences in the immune defense mechanisms for controlling HHV‐6 infection in CNS between pediatric and adult patients. In addition to the incidence, with regard to the clinical course of post‐transplant HHV‐6B encephalitis, acute limbic encephalitis is typical (Table ), and only a few pediatric patients with PALE have been reported . Thus, a meta‐analysis of large numbers of patients may help determine the precise incidence and clinical features of HHV‐6B encephalitis in pediatric HSCT patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As described above, various background factors are different between pediatric and adult HSCT recipients, but present study and together with the previous studies mainly analyzed adult patients suggest that there are any differences in the immune defense mechanisms for controlling HHV‐6 infection in CNS between pediatric and adult patients. In addition to the incidence, with regard to the clinical course of post‐transplant HHV‐6B encephalitis, acute limbic encephalitis is typical (Table ), and only a few pediatric patients with PALE have been reported . Thus, a meta‐analysis of large numbers of patients may help determine the precise incidence and clinical features of HHV‐6B encephalitis in pediatric HSCT patients.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher amount of viral DNA was detected in the cerebrospinal fluid (CSF) of PALE patients than in that of HHV‐6B encephalitis patients with primary viral infection . Additionally, the fact that antiviral treatments reduce viral DNA loads in CSF suggests that viral replication in the central nervous system (CNS) occurs in the PALE patients . However, since the prognosis of PALE patients remains poor despite antiviral treatment, preemptive, and prophylactic antiviral therapies have been attempted to improve prognosis …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…31,32 Antiviral CSF concentrations reach the therapeutic range in patients receiving full-dose foscarnet; 33 a case report suggested that this may not be the case in patients receiving full-dose ganciclovir. 34 Although the reasons why ganciclovir is associated with an increased risk of early death are unknown, myelosuppression owing to ganciclovir might increase the risk of infectious diseases. Combination therapy with foscarnet and ganciclovir seemed to be most effective in our study, but its evaluation is difficult because only 10 patients received the combination therapy and the doses of foscarnet and ganciclovir varied.…”
Section: Discussionmentioning
confidence: 99%